Effect of IBA and BAP on Shoot Growth of Tawangmangu Tangerine (Citrus reticulate) by In-Vitro - Sofian, Arif Ardianto; Prihastanti, Erma; Suedy, Sri Widodo Agung (Biosaintifika: Journal of Biology & Biology Education, 2018)
Tawangmangu tangerine (Citrus reticulate Blanco subsp. tawangmangu) is one of prime local fruit from Tawangmangu region, Karanganyar, Central Java. This tangerine have good appearance, easy to peeled, sweet flavored fruit, and high production rate. However at 1984 Tawangmangu tangerine run into depreciation of population caused by CVPD (Citrus Vein Phloem Degeneration). As a result, this variety listed as endangeredThe effort of consevation by culture tissue technique can order to obtain prime seeds that free from virus or disease. This study was aimed to understand the effect of IBA and BAP in culture medium on growth of apical and lateral shoot of Tawangmangu tangerine. The treatment provided were IBA (0 ppm, 0.5 ppm, and 1 ppm) and BAP (0 ppm, 1 ppm and 2 ppm). The treatment in this research was using complete randomized factorial design in 9 different treatment. This research resulted that added combination of IBA and BAP affecting growth of Tawangmangu tangerine but the interaction of IBA and BAP did not happen. The highest shoot length occurs on treatment IBA 1 ppm+BAP 2 ppm while when the fastest shoot appears occurs on treatment IBA 0 ppm+ BAP 2 ppm and the highest shoot formed on treatment IBA 0.5 ppm+BAP 2 ppm. Benefit of the research Efforts to conserve Tawangmangu orange plants need to be done to maintain the diversity of germplasm and support the cultivation in a manner. One technique that can support the conservation of plants is by tissue culture techniques.